Pancreatogenic diabetes mellitus: features of development, clinical course, diagnosis and treatment - Galina A. Batrak (LLC "MEDIAFORMAT", 2023)
The features of development, characteristic clinical symptoms, laboratory, instrumental methods of examination and the basic principles of therapy of pancreatogenic diabetes mellitus (DM) are determined. Correlations in the development and course of the disease were revealed. It has been proven that pancreatogenic diabetes occurs significantly more often in men, more than half of whom abuse alcohol and smoke, while after surgery for pancreatic necrosis, patients with pancreatogenic diabetes statistically significantly begin to drink less alcohol. According to a scientific study, the duration of pancreatogenic DM is closely interrelated with the duration of chronic pancreatitis. The low level of C-peptide confirms an early decrease in insulin secretion and, accordingly, the need for insulin therapy. Irregular intake of enzymes significantly contributes to exacerbations of chronic pancreatitis, worsens the course of diabetes and leads to the development of diabetic complications. It was noted that with the duration of pancreatogenic diabetes, the risk of hypoglycemia increases statistically significantly, which certainly requires regular blood glucose testing. Self-monitoring of blood glucose in patients with DM should be carried out with the help of modern, accurate and easy-to-use portable glucose meters, one of which is the Contour Plus Uan.